Degradation of polypropylene geotextiles with different chemical stabilisations in marine environments. (20th March 2018) - Carneiro, José Ricardo; Morais, Miguel; Lopes, Maria de Lurdes
Highlights: The exposure to weathering led to highest damage in the geotextiles. The weathering resistance of the geotextiles was highly enhanced by Chimassorb 944. Carbon black led to an additional protection of the geotextiles against weathering. The geotextiles had a good resistance against the action of seawater. The algae and dirt protected the geotextiles from UV-degradation (sunblind effect). Abstract: The geosynthetics applied in coastal engineering structures can be in contact with degradation agents capable of causing unwanted changes in their properties. In this work, three nonwoven polypropylene geotextiles with different stabilisation packages (different known amounts of Chimassorb 944 and carbon black) were exposed in situ to some degradation agents present in marine environments (weathering, seawater and action of tides). These exposures were carried out in Portugal (Archipelago of the Azores) and lasted for 36 months. The damage suffered by the geotextiles (in the different degradation tests) was evaluated quantitatively by monitoring changes in their physical (mass per unit area and thickness) and mechanical (tensile behaviour) properties. The results, among other findings, showed that: (1) weathering led to the highest damage in the geotextiles, (2) the weathering resistance of the geotextiles was highly enhanced by Chimassorb 944 and carbon black, (3) the geotextiles had a good resistance against the action of seawater and (4) the algae and dirt accumulated in the nonwoven structures during the exposure to the action of tides protected the geotextiles from UV-degradation (sunblind effect).